Formulation factors affecting the binding properties of chinese yam (dioscorea oppositifolia) and corn starches (2009)
Objective; The quantitative effects of formulation and processing variables affecting the binding properties of Chinese yam starch ( Dioscorea oppositifolia) in chloroquine phosphate tablet formulations have been investigated in comparison with com starch using a 23 factorial experimental design. Methods: Chinese yam starch, representing the "low" level, and com starch, representing the "high" level were used as binders at concentrations of 2. 5 % w/w and 10 % w/w in chloroquine phosphate tablet formulations. The mechanical properties of the tablets, measured by the tensile strength ( T ) and brittle fracture index ( BFI) as well as the release properties measured by the disintegration time (DT ) and dissolution time ( t80- time for 80 % drug release) , were used as assessment parameters. Results; The ranking of the individual coefficient values for the formulations on T was D > N » C , on BFI was N > D » C , on DT was D > N > C and on t80 was C > N > D while the ranking of the interaction coefficient on T was N-D > C-D » N-C, on BFI was N-D > N-C = C-D, on DT and t80 was N-C > N-D > C-D. Changing the binding agent from Chinese to corn starch, led to a decrease in T , DT and t80 but increase in BFI of the tablets. There were significant (P < 0 . 001) interactions between the nature of binder, N and the other two variables, C and D. Conclusion; The result showed that Chinese yam possessed stronger binding capacity than corn starch and could be useful as an alternative binder when tablets with high mechanical strength with minimal problems of lamination, and slow release are required.